O roli samooceny w edukacji językowej - opis warsztatu arteterapeutycznego = On the role of self-esteem in language learning and teaching - description of an art therapy workshop - Nieścioruk, Julia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article describes the implementation of an art therapy project which main goal was to strengthen the global self-esteem of participants - professionals taking part in the Summer School of Art Therapy - an event organized periodically by the Polish Art Therapists Association "Kajros." The event is intended to provide a supportive environment for art therapists, fostering positive relationships with their peers and equipping them with tools to enhance their self-esteem regarding their English language proficiency. Consequently, implementing measures to enhance self-esteem proves to be of significant importance.
Keywords: arteterapia; budowanie poczucia własnej wartości; samoocena związana z językiem obcym (L2); warsztaty arteterapeutyczne; art therapy; self-esteem improvement; second language (L2) self-esteem; art therapy workshops